Contingency Horizon: on Private Events and the Analysis of Behavior - Leigland, Sam (Behav Anal, 2014)
Skinner’s radical behaviorism incorporates private events as biologically based phenomena that may play a functional role with respect to other (overt) behavioral phenomena. Skinner proposed four types of contingencies, here collectively termed the contingency horizon, which enable certain functional relations between private events and verbal behavior. The adequacy and necessity of this position has met renewed challenges from Rachlin’s teleological behaviorism and Baum’s molar behaviorism, both of which argue that all “mental” phenomena and terminology may be explained by overt behavior and environment–behavior contingencies extended in time. A number of lines of evidence are presented in making a case for the functional characteristics of private events, including published research from behavior analysis and general experimental psychology, as well as verbal behavior from a participant in the debate. An integrated perspective is offered that involves a multiscaled analysis of interacting public behaviors and private events.